2005
DOI: 10.1111/j.1360-0443.2005.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there really a ‘J‐shaped’ curve in the association between alcohol consumption and symptoms of depression and anxiety? Findings from the Mater‐University Study of Pregnancy and its outcomes*

Abstract: The nature of the association between alcohol consumption and symptoms of depression and anxiety may vary across their life course in women. Previous drinkers who become abstainers do not appear to be at any higher risk of symptoms of depression or anxiety compared to those who always abstained, suggesting that increased symptoms in abstainers at age 30 is not due to 'sick quitters'. The association of high alcohol consumption with symptoms of depression and anxiety may be confounded by low income and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 23 publications
(32 reference statements)
9
90
2
8
Order By: Relevance
“…Day-to-day stresses, symptoms and hassles had a marked negative impact on women's well-being and subjective health, although their negative impact was minimized in those women who had moderate alcohol and tobacco use. This is consistent with limited existing evidence which suggests that intervening lifestyle, individual and family factors may attenuate the non-linear association between alcohol use and symptoms of mental health in women 8,12 . The finding that those who exercised frequently experienced a greater sense of wellbeing with increased alcohol intake may be partly explained by the contribution of physical activity to health and well-being already reported in this sample 20 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Day-to-day stresses, symptoms and hassles had a marked negative impact on women's well-being and subjective health, although their negative impact was minimized in those women who had moderate alcohol and tobacco use. This is consistent with limited existing evidence which suggests that intervening lifestyle, individual and family factors may attenuate the non-linear association between alcohol use and symptoms of mental health in women 8,12 . The finding that those who exercised frequently experienced a greater sense of wellbeing with increased alcohol intake may be partly explained by the contribution of physical activity to health and well-being already reported in this sample 20 .…”
Section: Discussionsupporting
confidence: 90%
“…A number of authors have previously investigated the effects of alcohol on individuals' mental health [6][7][8][9][10]12 . Some of these studies 6,7,9 , though not all 8 , have found a nonlinear association between alcohol intake and mental health status such that those who drank moderately were more likely to report fewer mental health problems when compared with both abstainers and heavier drinkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study Blow et al [27] reported that individual's at-risk and problem drinking elevated the risk of depressive symptoms. Results of a fourteen years longitudinal study revealed that at the baseline and 14-year follow-up alcohol consumption was linearly and positively associated with depressive symptoms; prevalence of symptoms increased with greater alcohol consumption [28]. Golstein, using a community survey, showed that the prevalence of depression increased significantly across drinking groups (i.e., 25% among minimal drinkers, to 30% moderate drinkers, to 44% among heavy drinkers) [29].…”
Section: Discussionmentioning
confidence: 99%